Evaluación de la respuesta productiva e inmune en juveniles de camarón Litopenaeus vannamei alimentado con mezclas probióticas - Campa-Córdova, Angel I.; Cristóbal, Yenni-Morales; Guzmán-Murillo, María A.; Aguirre-Guzman, Gabriel (Revista de Biología Marina y Oceanografía, 2020)
Shrimp diets with mixtures of probiotics (bacilli or yeasts) were evaluated on the production response and immunological effect on juvenile shrimp (Litopenaeus vannamei). The results showed a significant effect in growth, food consumption and feed conversion rate when probiotic diet was used. In addition, experimental diets with yeast mixture [C. insectorum (DH5), D. hansenii (DH6, and L1)] had a significantly higher amount of circulating haemocytes than those with bacilli [B. tequilensis (YC5-2), B. endophyticus (YC3-b) and B. endophyticus (C2-2)]. Shrimp fed both experimental diets (3x107 CFU mL-1) had a significantly higher growth and immune parameters when compared with the commercial diet. Both elements can contribute to the sustainable development and health of shrimp farming.